Correction to: Green Vertical-Cavity Surface-Emitting Lasers Based on InGaN Quantum Dots and Short Cavity - Yang, Tao; Chen, Yan‑Hui; Wang, Ya‑Chao; Ou, Wei; Ying, Lei‑Ying; Mei, Yang; Tian, Ai‑Qin; Liu, Jian‑Ping; Kuo, Hao‑Chung; Zhang, Bao‑Ping (Nano-Micro Letters, 2023)
Room temperature low threshold lasing of green GaN-based vertical cavity surface emitting laser (VCSEL) was demonstrated under continuous wave (CW) operation. By using self-formed InGaN quantum dots (QDs) as the active region, the VCSEL emitting at 524.0 nm has a threshold current density of 51.97 A cm−2, the lowest ever reported. The QD epitaxial wafer featured with a high IQE of 69.94% and the δ-function-like density of states plays an important role in achieving low threshold current. Besides, a short cavity of the device (~ 4.0 λ) is vital to enhance the spontaneous emission coupling factor to 0.094, increase the gain coefficient factor, and decrease the optical loss. To improve heat dissipation, AlN layer was used as the current confinement layer and electroplated copper plate was used to replace metal bonding. The results provide important guidance to achieving high performance GaN-based VCSELs. Highlights: 1 Continuous-wave green vertical-cavity surface-emitting lasers based on self-formed quantum dots were realized with the lowest threshold current density of 51.97 A cm−2. 2 A short cavity (~4.0 λ, where λ is the wavelength in the media) was adopted to enhance the interaction between spontaneous emission and lasing mode, with a big coupling factor up to 0.094. 3 AlN current confinement layer and the electroplated supporting copper plate were utilized to improve heat dissipation, with a low thermal resistance of 842 K W−1.